Comparative studies of bismuth and barium boro-tellurite glass system: structural and optical properties - Amat, Azuraida; Mohamed Kamari, Halimah; Abd. Aziz, Sidek; C. A. C., Azurahanim; Mustafa, Iskandar Shahrim; M., Ishak; A., Nurazlin (Institutul National de Cercetare-Dezvoltare Pentru Fizica Materialelor,National Institute of Research and Development of Materials Physics, 2015)
This paper aims to compare the structural and optical properties of ternary Boro-tellurite glass with the addition of two different chemical modifier. Six glass samples from composition [(TeO2)0.7 (B2O3)0.3]1-x (BaO)x (x = 0.10, 0.20 and 0.30 mol%) and [(TeO2)0.7 (B2O3)0.3]1-x (Bi2O3)x (x = 0.10, 0.20 and 0.30 mol%) were prepared by melt quenching method with suitable melting and quenching temperature. The X-ray diffraction (XRD) pattern confirms the amorphous nature of all glasses and the Fourier transform infrared spectroscopy (FTIR) spectra explore the fundamental groups and the local structural units in two different boro-tellurite glasses. The density for both glass series increased as barium oxide and bismuth oxide content increased. The optical band gap, Eopt values for bismuthboro-tellurite glasses are between 2.15–2.4 eV, while barium-boro-tellurite glasses are between 2.25–2.44 eV. The highest concentration of Bi2O3 in glass system shows the smallest Eopt. In conclusion, the obtained results shows that the addition of bismuth oxide in boro-tellurite glass improves its structural and optical properties.